Cyclic Microwave-Assisted Metathetic Synthesis and Spectroscopic Properties of SPION/SrWO4:Er3+, Yb3+ Composites - Sung Lim, Chang (Asian Journal of Chemistry, 2014)
Er3+/Yb3+ co-doped SrWO4(SrWO4:Er3+/Yb3+) composites with superparamagnetic iron oxide nanoparticles (SPIONs) were successfully synthesized by a cyclic microwave-assisted metathetic method followed by heat-treatment. The microstructure exhibited well-defined and homogeneous morphology with the SrWO4:Er3+/Yb3+ particle size of 1-2 μm and Fe3O4 particle size of 0.1-0.5 μm. The Fe3O4 particles were self-preferentially crystallized and immobilized on the surface of SrWO4:Er3+/Yb3+ particles. The synthesized SPION/SrWO4:Er3+/Yb3+ composites were characterized by X-ray diffraction, scanning electron microscopy and energy-dispersive X-ray spectroscopy. Other spectroscopic properties were also examined using photoluminescence emission measurements and Raman spectroscopy.